2019
DOI: 10.3776/tpre.2019.v9n2p65-78
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Student and Preservice Teacher Successes Through Co-teaching

Abstract: As increasing inclusion in schools has been emphasized with each reauthorization of the Individuals with Disabilities Education Act amendments, the implementation of co-teaching has increased. Co-teaching has emerged as a supportive framework that uses principles of social justice in building inclusive nurturing environments, yielding positive student outcomes in social as well as academic areas of education. The authors explored the use of co-teaching within a laboratory school setting by analyzing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
5
0
4
Order By: Relevance
“…In this study, it is revealed that in classes given with the co-teaching method, not only students with special needs, but also their peers (and even at higher ratios, see Table 1) have positive opinions about willingness, expectations and self-evaluation as well as academic success. In fact, with emphasis on literature Lersch (2012) and Barron et al (2019) stated that co-teaching may not be sufficiently effective to produce high-level academic results for students, but that it can make various positive contributions (interaction between students with special needs and normally developing students, enjoying the lessons , effective implementation of the curriculum, social, emotional and behavioural growth etc.) which should not go unnoticed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this study, it is revealed that in classes given with the co-teaching method, not only students with special needs, but also their peers (and even at higher ratios, see Table 1) have positive opinions about willingness, expectations and self-evaluation as well as academic success. In fact, with emphasis on literature Lersch (2012) and Barron et al (2019) stated that co-teaching may not be sufficiently effective to produce high-level academic results for students, but that it can make various positive contributions (interaction between students with special needs and normally developing students, enjoying the lessons , effective implementation of the curriculum, social, emotional and behavioural growth etc.) which should not go unnoticed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Teachers often feel undertrained to work with students who misbehave regularly (Cochran et al, 2014). One way to address this concern is by having a highly qualified special education teacher co-teach with the general education teacher to address misbehavior in the classroom (Barron et al, 2019;Strogilos & Avramidis, 2016). Co-teaching is when two or more professionals provide instruction to a group of students (Hang & Rabren, 2009;Murawski & Hughes, 2009).…”
Section: Co-teaching Interventionmentioning
confidence: 99%
“…Una definición más reciente indica que la DC es la prestación de servicios que proporciona ayuda específica a estudiantes con diversidad funcional u otras necesidades especiales mientras permanecen en sus clases de aula ordinaria (Aldabas, 2020). Por lo tanto, la DC ocurre cuando dos o más profesionales llevan a cabo conjuntamente la enseñanza en una misma aula y a un mismo grupo de estudiantes, sirviendo como una estrategia de enseñanza en el aula y como una estrategia para el desarrollo del profesorado (Barron, Pinter & Winter, 2019;Lindacher, 2020). La DC se relaciona estrechamente con la gestión del aula y del currículum.…”
Section: Origen Y Aproximación Al Concepto De Docencia Compartida: Beneficios E Inconvenientesunclassified
“…Existen numerosas experiencias que muestran la eficacia de la DC en el desarrollo integral del alumnado, principalmente cuando los docentes la realizan con una cierta continuidad en el tiempo, resaltando y expresando la satisfacción que sienten tras la puesta en práctica de la misma (Friend & Cook, 2013). En este sentido, multitud de investigaciones (Porras-Vallejo, 1998;Aretxaga, Palacios & del Berritzegune, 2014;Hurd & Weilbacher, 2017;Boland, Alkhalifa & Al-Mutairi, 2019;Barron, Pinter & Winter, 2019) resaltan los beneficios que como docentes no debemos obviar de la DC:…”
Section: Origen Y Aproximación Al Concepto De Docencia Compartida: Beneficios E Inconvenientesunclassified
See 1 more Smart Citation